Study of the Placement of Fire Extinguishers at the Kartini Rembang Museum using Space Syntax Analysis - Emhade Arman Erhaqim; Siti Zulfa Yuzni (International Journal of Built Environment and Scientific Research, 2024)
The RA Kartini Museum in Rembang plays a crucial role role as the caretaker of arts collections and historical artifacts. This study emphasizes the importance of the presence of Fire Extinguishers in ensuring the security of themuseum. The strategic placement of fire extinguisher points, considering accessibility and visibility, is the focal point for enhancing response and safety. Evaluation of the existing fire extinguisher layouts fixed to ensure compliance with safety standards. The Kartini Museum, located within the Rembang Regency, operates as the residence of the regent and has now become a Cultural Heritage site. The museum's collection fixed to RA Kartini, with exhibition spaces encompassing various types of collections. This research employs the Space Syntax method to analyze spatial connectivity and visual integration. The analysis results indicate that the placement of fire extinguishers in some rooms already exceeds safety standards. However, the presence of fire extinguishers needs to be reinforced with clear and easily locatable signage. Some fire extinguishers are obstructed by shelves or columns, and their placement requires review to ensure efficient accessibility. In conclusion, this study provides a foundation for strategic changes in the placement of fire extinguishers in the Kartini Museum. Recommendations include improved signage, a reevaluation of placement, and enhancements to accessibility. These measures will enhance safety and response to the potential threat of fire, preserving invaluable cultural heritage.